1993
DOI: 10.1017/s0950268800051062
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofGiardiasp. cysts andCryptosporidiumsp. oocysts in faeces from public parks in the west of Scotland

Abstract: SUMMARYOne hundred faecal specimens, randomly collected from various locations within seven public parks in the west of Scotland, were examined for the presence of Giardia sp. cysts and Cryptosporidium sp. oocysts. Eleven percent of samples contained Giardia sp. cysts and 1 % contained Cryptosporidium sp. oocysts. Occurrence data from individual parks varied from 0 to 40 % for Giardia and 0 to 2 4 % for Cryptosporidium. The occurrence of parasitic organisms in public parks, especially in the vicinity of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…infection in PA dogs that were kept on-leash, and NPA dogs. This is probably because off-leash dogs are more exposed to environmental contamination from sources like undisposed dog faeces [13,[19][20][21] than on-leash PA, and NPA dogs. Although Wang et al [18] did not consider behaviours within parks as potential confounders for the association they found between park attendance and infection with Giardia spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…infection in PA dogs that were kept on-leash, and NPA dogs. This is probably because off-leash dogs are more exposed to environmental contamination from sources like undisposed dog faeces [13,[19][20][21] than on-leash PA, and NPA dogs. Although Wang et al [18] did not consider behaviours within parks as potential confounders for the association they found between park attendance and infection with Giardia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Within the social sciences, investigations into the relationships between spatial and temporal patterns of dog-walking, dog-to-dog contact, and dog demographics have indirectly explored behaviours that could influence the risk of GI disease transmission in dogs [3,[11][12][13]. However, only a limited number of studies have investigated the extent to which parks might pose risks for infection and transmission of GI parasites in dogs [2,7,9,[13][14][15][16][17][18][19][20][21], a relevant query given that in urban settings, parks figure prominently as dog-walking destinations [22]. Giardia spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers suggested that prevalence may be highest in dogs from rural environments, since Cryptosporidiosis is primarily associated with farm livestock (Causape et al, 1996). Grimason et al (1993) and coworker found 1% of the faecal specimen collected in seven public parks in Scotland contained Cryptosporidium oocysts, with a prevalence in individual parks ranging from 0-2.4%. In this study, no statistical differences between infection with Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few comprehensive epidemiological surveys on dog cryptosporidiosis in Europe, and the existing data have mainly relied on studies with light microscopy. A prevalence ranging from 1 to 7% in both privately owned and stray dogs has been reported in some countries, such as France (Chermette and Blondel 1989), Scotland (Grimason et al 1993) and Spain (Diaz et al 1996). In Italy, only one confirmed case of clinical cryptosporidiosis has been reported in a dog in Lombardy (Traldi 1990), and no studies regarding the prevalence of canine cryptosporidiosis are available.…”
Section: Introductionmentioning
confidence: 99%